2004
DOI: 10.1152/ajpheart.00215.2004
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of control of muscle sympathetic nerve activity during orthostatic stress in humans

Abstract: We tested the hypothesis that orthostatic stress would modulate the arterial baroreflex (ABR)-mediated beat-by-beat control of muscle sympathetic nerve activity (MSNA) in humans. In 12 healthy subjects, ABR control of MSNA (burst incidence, burst strength, and total activity) was evaluated by analysis of the relation between beat-by-beat spontaneous variations in diastolic blood pressure (DAP) and MSNA during supine rest (CON) and at two levels of lower body negative pressure (LBNP: -15 and -35 mmHg). At -15 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 38 publications
9
30
0
Order By: Relevance
“…Therefore, it seems obvious that similar response from MI sequence could not occur and parallel those observed during actual trunk movement eliciting orthostatic hypotension. Ichinose et al (2004) and Kamiya et al (2005) suggested that the upward resetting of arterial baroreflex control in response to orthostatic stress facilitates the activation of sympathetic nerve activity, thereby contributing to the prevention of postural hypotension. Muscle sympathetic nerve activity progressively increases in response to increasing orthostatic stress through the gradual upward resetting of arterial baroreflex control.…”
Section: The Autonomic Nervous System: a Witness Of Movement Observatmentioning
confidence: 99%
“…Therefore, it seems obvious that similar response from MI sequence could not occur and parallel those observed during actual trunk movement eliciting orthostatic hypotension. Ichinose et al (2004) and Kamiya et al (2005) suggested that the upward resetting of arterial baroreflex control in response to orthostatic stress facilitates the activation of sympathetic nerve activity, thereby contributing to the prevention of postural hypotension. Muscle sympathetic nerve activity progressively increases in response to increasing orthostatic stress through the gradual upward resetting of arterial baroreflex control.…”
Section: The Autonomic Nervous System: a Witness Of Movement Observatmentioning
confidence: 99%
“…During mild to moderate central hypovolemia, the operating point of baroreflex-mediated control of sympathetic nerve activity is shifted upward without a change in gain, such that sympathetic nerve activity is increased at any given DAP (Ichinose et al, 2004a,b). Additionally, there is a tighter coupling between oscillations in arterial blood pressure and MSNA, as quantitated using cross-spectral analysis by an increase in the coherence function between these variables (Furlan et al, 2000; Kamiya et al, 2005; Cooke et al, 2009).…”
Section: Msna At Hemodynamic Decompensationmentioning
confidence: 99%
“…Large increases of baroreflex gain occur when supine subjects sleep (Smyth et al , 1969, Pagani et al , 1988), and when upright subjects abruptly return to the supine position (Westerhof et al , 2006). Moreover, simple repeated estimates of vagal baroreflex gain in subjects who are, as well as can be determined, in a ‘steady-state’, document surprisingly large ongoing fluctuations of vagal baroreflex gain (Yamamoto et al , 1989, Badra et al , 2001, Ichinose et al , 2004, Eckberg & Kuusela 2005). …”
Section: Discussionmentioning
confidence: 99%